The Role of Punk Music in the Formation of Adolescent Identity in Dušan Dim’s Novel Distorzija - Tušar, Ajda; Laure, Maruša (Trideset let literarne nagrade večernica, 2026)
This paper examines the relationship between music and adolescence, with a particular focus on the role of music in the formation of adolescent identity. Drawing on theoretical perspectives on adolescent development, the importance of peer relationships, and the functions of music, punk music is presented as an expression of rebellion, self-affirmation, and social criticism. The central part of the paper is an analysis of the young adult musical novel Distorzija by Dušan Dim, which received the Večernica Award for children's and young adult literature. The study explores the interplay of musical, socio-psychological, and romantic novel elements, the role of punk music in shaping the protagonist’s identity, and the significance of musical references in conveying the novel’s message. The findings indicate that music in the novel functions not merely as a background element but as a central means of expression through which the protagonist constructs his worldview, expresses resistance to authority, and develops his personal identity.